Organ preservation, for rectal cancer: general overview of the latest data from phase III randomized trials - Syrine Ben Dhia; Damien Chauviere; Diana Mitrea; Renaud Schiappa; Tanguy Pace Loscos; Emmanuel Chamorey; David Baron (Acta Oncologica)
Introduction: Organ preservation (OP) strategies are gaining interest in improving the quality of life in the management of rectal cancer, particularly for tumors located in the distal or middle rectum. The optimal OP protocol is still not standardized and relies on randomized trials. This review summarizes past and ongoing studies on OP protocols for adenocarcinoma of the distal and middle rectum.